Réponses

2013-11-03T20:01:26+01:00
X(x+2)-(2x-1)(x+2)
forme développé : x²+2x-(2x²+4x-x-2)
                          x²+2x-2x²-4x+x+2
                          -x²-x+2
forme factorisé : (x+2)(x-(2x-1))
                         (x+2)(x-2x+1)
                          (x+2)(-x+1)
2013-11-03T20:02:45+01:00
x (x+2) - (2x-1)(x+2)
x²+2x-(2x²+4x-x-2)
=x²+2x-2x²-4x+x+2
=-x²-x+2

(x+2)(-x + 1)
=-x²+x-2x+2
=-x²-x+2

donc x (x+2) - (2x-1)(x+2)  est la forme factorisée de (x+2)(-x + 1)
Merci))
http://nosdevoirs.fr/devoir/153996 SVP il y a personne qui m'aide ...